Assessment of the drivers of extinction risk of tropical mammal and birds - Manrique López, Hernán Arturo (2020)
The loss of biodiversity and species is one of the greatest contemporary challenges for the Earth system. Nowhere are these current losses as great as in tropical forests. However, an important part of the concerns about the state of biodiversity are based on the possible negative impacts on the ecosystem services that humans enjoy. Against this anthropocentric bias when evaluating the relevance of biodiversity loss, this thesis focuses its attention on other non-human forms of life threatened by anthropogenic pressures. In this way, it aims to respond to what are the drivers of the threat of extinction of mammals and birds in the tropics. The results underline the overall importance of geographic characteristics above other socioeconomic predictors. All models presented the insular factor as the most important element in advancing the risk of extinction of both mammals and birds. Continuous predictors such as population density, grain yield, and GDP were recurrently associated with increased odds of being at risk.